2019
DOI: 10.3390/vetsci6010031
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of BRAF Variant V595E, Breed, Histological Grade and Cyclooxygenase-2 Expression in Canine Transitional Cell Carcinomas

Abstract: The presence of BRAF variant V595E, as well as an increased cyclooxygenase-2 (COX-2) expression in canine transitional cell carcinoma (TCC) are well-described in the literature. The aim of the present study was to investigate the correlation between breed (terrier versus non-terrier dogs), histological grade, COX-2 expression, and BRAF mutation in canine TCC. Therefore, transmural TCC biopsies from 65 dogs (15 terriers, 50 non-terriers) were graded histologically into low- and high-grade. Immunohistochemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 51 publications
7
31
2
Order By: Relevance
“…From this study, since BRAF mutation was associated with pERK IHS score and pERK IHS score was clearly associated with COX2 expression, we believe that BRAF mutation would contribute to the overexpression of COX2 in cUC although the direct causal relationship of them should be further examined. In a recent study, the association between BRAF mutation and COX2 expression was suggested in cUC tissues in specific dog breeds 48 .…”
Section: Discussionmentioning
confidence: 99%
“…From this study, since BRAF mutation was associated with pERK IHS score and pERK IHS score was clearly associated with COX2 expression, we believe that BRAF mutation would contribute to the overexpression of COX2 in cUC although the direct causal relationship of them should be further examined. In a recent study, the association between BRAF mutation and COX2 expression was suggested in cUC tissues in specific dog breeds 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In the histological analysis, BRAF mutant cUC cells tended to show higher expression of COX2. In a recent study, the association between BRAF mutation and COX2 expression was only observed in cUC tissues of specific dog breeds 40 . Further, in our in vitro study, one of the BRAF mutant cUC cell lines did not overexpress COX2 and…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a commercially available diagnostic test was developed to non-invasively detect the BRAF V595E mutation in cells shed into the urine using droplet PCR. However, this mutation is only present in the urine of ~65-80% of dogs with MIUC [150,151], prostate cancer [151] and other types of canine cancers [145,152] making it non-specific for UC. In addition, the presence of the BRAF V595E mutation might be breed specific.…”
Section: Braf V595e Mutation As a Diagnostic Biomarker In Canine Ucmentioning
confidence: 99%
“…In addition, the presence of the BRAF V595E mutation might be breed specific. A study examining MIUC tissues from dogs of different breeds found that the presence of the BRAF V595E mutation is more frequent in terriers (n = 15, 73%) compared to non-terriers with MIUC (n = 50, 36%) (p < 0.05) [152].…”
Section: Braf V595e Mutation As a Diagnostic Biomarker In Canine Ucmentioning
confidence: 99%